2021
DOI: 10.1177/08862605211021972
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors of Inpatient Verbal Aggression in a Forensic Psychiatric Setting Using a Tree-based Modeling Approach

Abstract: Inpatient violence poses a great risk to the health and well-being of other patients and members of staff. Previous research has shown that prevalence rates of violent behavior are particularly high in forensic psychiatric settings. Thus, the reliable identification of forensic inpatients who are particularly at risk for violent behavior is an important aspect of risk management. In the present study, we analyzed clinicians’ assessments of N = 504 male and female inpatients of German forensic mental health ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…A retrospective study on the characteristics of NCRMD patients in the psychiatric hospitals of France found that the majority of the patients were diagnosed with psychotic disorder (61.8%), and young persons and males were overrepresented [22]. A study [23] in Germany partially supported these findings, in which 92.5% of patients were male with mean age of 39.1 years (SD: 11.5); while in this study the majority of diagnosis were substance use disorder (69.2%), while schizophrenic disorders were 24.2%, which may suggest that the characteristics of forensic patients may differ across jurisdiction.…”
mentioning
confidence: 99%
“…A retrospective study on the characteristics of NCRMD patients in the psychiatric hospitals of France found that the majority of the patients were diagnosed with psychotic disorder (61.8%), and young persons and males were overrepresented [22]. A study [23] in Germany partially supported these findings, in which 92.5% of patients were male with mean age of 39.1 years (SD: 11.5); while in this study the majority of diagnosis were substance use disorder (69.2%), while schizophrenic disorders were 24.2%, which may suggest that the characteristics of forensic patients may differ across jurisdiction.…”
mentioning
confidence: 99%
“…5,6 Core dispositional factors such as personality pathology and other severe psychiatric disturbances directly determine the extent to which patients can achieve such adaptation. [7][8][9][10][11][12][13][14][15][16] However, more contextual factors, such as the institutional climate, have also been proposed. 17 Building on this contextual perspective, in this article we explore whether the therapeutic alliance between forensic patients in long-stay units and their counselors also plays a significant role in the way patients adapt to the institutional context.…”
mentioning
confidence: 99%
“…Recently, there have been applications of decision tree methods in mental health research given it automatizes detection of main effects and interactions [13]. The advantage of using tree-based models in this study is that they can handle complex relationships between predictors and outcomes, such as intricate interaction effects [14]. Additionally, tree-based models provide an interpretable and intuitive visualization method that can be easily communicated to clinicians [14].…”
mentioning
confidence: 99%
“…The advantage of using tree-based models in this study is that they can handle complex relationships between predictors and outcomes, such as intricate interaction effects [14]. Additionally, tree-based models provide an interpretable and intuitive visualization method that can be easily communicated to clinicians [14]. By identifying factors that increase an individual's likelihood of having higher levels of trait NA, this study may lead to more targeted interventions aimed at reducing NA and improving mental health outcomes in both depressed and nondepressed adults.…”
mentioning
confidence: 99%